Trade and Migration with Renewable Natural Resources : Out-of-Steady-State Dynamics - López, Ramón; Schiff, Maurice (2012)
Commodity price increases associated with the entry of China, India, and other countries into the world economy have led to increased pressure on common-property renewable natural resources. The problem is particularly worrisome for economies that obtain a large share of their income from the exploitation of natural resources in the production of an exportable commodity. This paper contributes to the analysis by examining the issue in the framework of a general equilibrium dynamic model and by solving for both the steady state and the transition dynamics. The authors show that i) a resource-rich, capital-poor economy is more likely to be subject to a "natural resource curse" and complete (irreversible) depletion of natural resources; ii) the latter's likelihood rises with the relative commodity price and labor inflow; iii) a labor inflow under internal equilibrium results in a higher steady-state capital-labor ratio and manufacturing output, and unchanged natural resources and commodity output; iv) import and export taxes result in larger steady-state natural resources and commodity output and smaller capital stock and manufacturing output, and may prevent complete depletion of natural resources; and v) the latter may also be prevented through capital inflows (foreign aid), labor outflow ( liberalization of the North's immigration policy), improved regulation, technical change, and a production tax.